Hydrothermal synthesis of vanadium dioxide nanoparticles codoped with magnesium/tungsten - Tang, Kai Wen (2016)
Vanadium dioxide (VO2) is a compound that exhibits a reversible phase transition, which makes it one of the most promising candidates for the usage of smart window coatings as a thermochromic material. For a pure VO2 that contains no doping, the phase transition occurs at 68°C which is relatively much higher than the room temperature of 25°C. This means that the high Tc it exhibits as well as the low ΔTsol and Tlum limit its practical applications as a thermochromic material for the smart window coatings in an ambient temperature. However with the addition of other elements as dopants to the VO2, it can decrease the Tc to ambient temperature, close to 25°C. In this report, codoping with Mg/W was proposed to modify the thermochromic properties of VO2. Doping W itself will not also result in a decrease in Tc but also ΔTsol and Tlum as well, hence Mg was codoped with W to counteract the decrease in ΔTsol and Tlum. Codoping Mg/W can effectively reduce the Tc to 37.2°C and give a ΔTsol and Tlum of 3.9% and 53.1% respectively, at 5 at.% Mg codoped with W in VO2. This suggests that the method of codoping Mg/W in VO2 thin films can effectively modulate the thermochromic properties of the VO2 films.